SIKENA: Digitalization of BUMDes management in Mario Village - Zikra Supri; Wisnu Kurniadi; Rismawati Sudirman; Goso Goso (Community Empowerment, 2023)
The manager of BUMDes Mario does not have sufficient knowledge to manage BUMDes, especially the financial aspects in the form of accounting reports. The purpose of this service activity is to increase partners' knowledge and skills related to financial management and to provide a simple accounting system application (SIKENA) for BUMDes. The method of implementing this community service consists of four stages, namely, Focus Group Discussion (FGD), making applications, testing applications and evaluating program implementation. The results of the program include increasing the knowledge and skills of partners related to financial management. In addition, a simple accounting application is available.